The relationship between alcohol abuse and homicides in the sample of convicted offenders in Belgrade - Ignjatović Đorđe; Lukić Natalija (Anali Pravnog Fakulteta u Beogradu)
This paper examines the relationship between alcohol abuse and homicides. The first part explores the relevance of alcohol in violent crime in general as well as in homicides. The authors further analyse criminology theories that explain the influence of this factor in understanding homicides. The second part of the article is an empirical analysis of a sample of 84 final court cases of the High Court in Belgrade, involving 105 victims, with the total 95 persons convicted of homicide, aggravated homicide or manslaughter. In addition to determining the prevalence of alcohol abuse in the sample, the authors also analyse the significance of the presence of alcohol in different homicide classifications. Authors conclude that the most relevant is the classification into conflict, revenge, intimate partner and homicides committed during robbery. The classification of homicides into expressive and instrumental, and homicides between strangers or acquaintances is not statistically significant.